The temperament police. - Tidhar, Dan; Dixon, Simon; Benetos, Emmanouil; Weyde, Tillman (Early Music, 2014)
Keyboard temperaments have been extensively discussed in historical treatises as well as more recent scholarly texts. The work presented in this article aims to provide a unique perspective on the subject, by applying signal processing techniques for estimating the temperaments used in harpsichord solo recordings, to show what is done in practice, thus facilitating a descriptive approach to tuning and temperament.Motivations, previous work, current methods and results obtained from a dataset which currently includes over 2,000 tracks from over 90 harpsichord solo CDs are discussed, together with some of the implications of these results, and the directions this work may take in the future.